SAT0307 PROGRESSION OF SUBCLINICAL MYOCARDIAL INVOLVEMENT IN PATIENTS WITH SYSTEMIC SCLEROSIS. (2nd June 2020) - Benfaremo, D.; Stronati, G.; Manfredi, L.; Zuliani, L.; Ferrarini, A.; Fischetti, C.; Dichiara, C.; Guerra, F.; Dello Russo, A.; Gabrielli, A.
Abstract : Background: Systemic sclerosis (SSc) is a progressive autoimmune disease affecting the skin as well as internal organs, including the heart. A few studies have identified a subclinical heart involvement in patients with no pulmonary hypertension. Changes in myocardial deformation are consistent with the idea of SSc-related cardiomyopathy as a primary condition affecting the heart globally through microvascular dysfunction and subsequent myocardial fibrosis. Objectives: The aim of the present study is to describe the progression of myocardial deformation in patients with SSc and no overt cardiac disease. Methods: Prospective longitudinal study enrolling consecutive SSc patients referred to the Clinica Medica, University Hospital 'Ospedali Riuniti', Ancona, Italy, from February 2016 to December 2018. All patients fulfilled the 2013 ACR/EULAR classification criteria for SSc. Patients with structural heart disease, heart failure, atrial fibrillation or pulmonary hypertension were excluded. Disease subset, antibodies pattern, cardiovascular risk factors and involvement of other organ systems were recorded for each patient. An echocardiographic exam was performed for all patients at baseline and during their follow-up evaluation. Standard and speckle-tracking derived variables for the systolic and diastolic function of the left ventricle (LV) and right ventricle (RV) were acquired. Speckle tracking analysis software (EchoPAC 13.0; GE Medical Systems, Milwaukee, USA) was used to assess the GLS of the left and right ventricle, excluding the ventricular septum from right ventricular GLS calculations. Results: Seventy-two patients (68 females, age 56.6±15.4 years) were enrolled. Common echocardiographic parameters of left and right systolic function were within normal range at baseline and did not change during follow-up. Mean GLS, however, worsened for both left (from -19.8±3.5% to -18.7±3.5%, p=.034) and right ventricle (from -20.9±6.1% to -18.7±5.4%, p=.013) during a median follow-up of 20 months (1st-3rd quartile 12-24 months). The increased impairment registered in SSc patients was homogenous across endocardial layers (LV from -22.5±-3.9 to -21.4±3.9, p=.041; RV from -24.2±6.2 to -20.6±5.9, p=.001), mesocardial layers (LV -19.7±3.6 to -18.7±3.5, p=.043; RV from -21.3±5.9 to -18.8±5.7, p=.012) and epicardial layers (LV from -17.1±3.0 to -16.4±3.1, p=.112, RV -18.8±6.3 to -16.0±8.4, p=.035), as well as myocardial segments. No difference in progression rate was observed stratifying patients according to disease subset or other clinical parameters. Conclusion: GLS impairment progressed over a 20-month follow-up period in a cohort of SSc patients without clinically overt cardiac involvement. Further studies are needed to assess the significance of subclinical heart involvement and its progression in patients with SSc. Disclosure of Interests: None declared